Implementing a like-industrial process for control education (2019)
Nowadays, one of the main difficulties experienced by engineering students is the ability to assimilate theoretical concepts and apply them in practice, especially in the industrial field. Although there are different educational prototypes in the market, these are generally expensive and their constructive details are not accessible to the user. This paper describes the implementation of a didactic equipment for the independent control of two variables, level and flow. The equipment allows to select a type of control equipment, PLC or SLC and can also show the process variables in real time in an HMI panel. © 2019 IEEE.